2007
DOI: 10.1002/ajmg.a.32088
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoarthrosis of the clavicle and copper beaten skull associated with chromosome 10p11.21p12.1 microdeletion

Abstract: Congenital pseudoarthrosis of the clavicle (CPC) has been described in several genetic conditions including Floating-Harbor and Goltz syndromes, but rarely as a prompt to specific cytogenetic abnormalities. We report on a case of a de novo 10p11.21p12.1 microdeletion in a boy with multiple problems including a beaten copper appearance of the cranium on skull X-ray and pseudoarthrosis of the right clavicle. This is the first description of these particular skeletal findings in the context of a chromosome 10p de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…Our six patients share some features with the previously described patient with a 10p12-p11 deletion. 5 Clinical data for this patient are summarised in Table 1 (genomic data kindly provided by Dr Nicole de Leeuw chr10: 26.901.972-36.934.901 (hg18)). The similarities between our six patients and the patient reported in the literature included DD and a majority of the patients have abnormal behaviour and dysmorphic features, including bulbous nasal tip, deep set eyes, synophrys/thick eyebrows and full cheeks, whereas other features varied.…”
Section: Molecular Results Of the Six Patients Are Summarised Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Our six patients share some features with the previously described patient with a 10p12-p11 deletion. 5 Clinical data for this patient are summarised in Table 1 (genomic data kindly provided by Dr Nicole de Leeuw chr10: 26.901.972-36.934.901 (hg18)). The similarities between our six patients and the patient reported in the literature included DD and a majority of the patients have abnormal behaviour and dysmorphic features, including bulbous nasal tip, deep set eyes, synophrys/thick eyebrows and full cheeks, whereas other features varied.…”
Section: Molecular Results Of the Six Patients Are Summarised Inmentioning
confidence: 99%
“…There is one previous report of a patient with DD and dysmorphic features presenting with a microdeletion within this region detected with arrayCGH. 5 The seven patients share some phenotypic traits and dysmorphic features. We describe the phenotypic traits that are shared between all individuals and suggest that microdeletions of 10p12.31p11.21 might be associated with a new clinically recognisable microdeletion syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…(b) The genomic region involved in the 10p12p11 contiguous gene deletion region with the previously published microdeletions, represented by gray horizontal bars. [14][15][16] (c) Detailed view of the smallest region of overlap (SRO) and the deletion described in this study, represented by a red horizontal bar. In addition, de novo mutations in WAC (NM_016628.3) reported in this study are shown according to their relative position at protein level.…”
Section: Identification Of Individuals With De Novo Cnvs Affecting Wacmentioning
confidence: 99%
“…The shortest region of deletion overlap of the chromosome 10p12p11 contiguous gene deletion syndrome was previously determined by nine deletions ranging in size between 0.99 and 10.66 Mb. [14][15][16][17] Comparison of the deletion in Individual 2 to the shortest region of deletion overlap indicates WAC as a only remaining candidate gene for the ID phenotype (Figure 1b).…”
Section: Identification Of Individuals With De Novo Cnvs Affecting Wacmentioning
confidence: 99%
See 1 more Smart Citation